User perception evaluations of 3D video telephony as compared to actual experience for face-to-face immersive communications - Mohd Arif, Nor Azhar; Abdul Karim, Hezerul; Mohamad, Hafizal; Sali, Aduwati; Mokhtar, Mohd Ridzuan (IEEE, 2011)
User perception evaluations of an experimental 3D video communication system are conducted utilizing bilateral experimental setup. Subjective assessment method together with the 5-grade ITU-R quality and impairment scales are adopted in these evaluations. Two sets of experimental system are installed in two evaluation booths to emulate video communication between two users at two different locations. Evaluation items are categorized into two namely 3D effects related and system related. The results indicate that video communication through the system shows positive closeness to natural face-to-face communication and the eye contact level during video communication is the only significant limitation of the experimental system thus requires improvement.